Evaluation of nutritional status in children hospitalized in Mofid Children’s Hospital, Tehran, Iran - Sayyari, Ali-Akbar; Imanzadeh, Farid; Moradi, Mehdi; Javaherizadeh, Hazhir; Shamshiri, Ahmad-Reza (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Children who are admitted to the hospital are at high risk of developing malnutrition. Malnutrition may cause complication during and after hospitalization. Aim : To determine the frequency of weight reduction among children hospitalized in a tertiary referral hospital in Tehran. Material and methods Patients aged  1 month and length of hospital stay > 48 h were included in this study. Duration of this study was 3 months from 1st November 2006. Age, sex, disease severity, respiratory difficulty, calorie intake, diarrhea, vomiting, dysphagia, length of hospital stay, and type of disease (surgical vs. medical) were assessed during admission. Children with weight reduction < 2% were placed in group I. Data were analyzed by SPSS ver. 14.0 (Chicago, IL, USA). Results : In this study 322 cases were included. Group I included 156 patients (48.44%) and group II included 110 patients (51.56%). One hundred and fifty patients (46.6%) had caloric intake less than 50% and 172 (53.4%) had caloric intake  50%. Analysis showed that calorie intake equal to or less than 50%, disease grade 2 and 3, duration of hospital stay, diarrhea, and dyspnea had a significant correlation with weight reduction  2% (p < 0.05). Conclusions : Calorie intake < 50%, disease severity, length of hospital stay, diarrhea, and dyspnea were significantly higher among cases with weight reduction  2% than cases with weight reduction < 2%.